1998
DOI: 10.1002/(sici)1097-0215(19980610)76:6<897::aid-ijc21>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of growth of hepatocellular carcinoma by sodium butyrate in vitro and in vivo

Abstract: Treatment of HuH-7 human hepatocellular carcinoma (HCC) cells with 1-10 mM sodium butyrate (SB) resulted in growth inhibition in a dose-dependent manner. At 3 mM and higher concentrations, SB caused nuclear fragmentation and DNA ladder formation characteristic of apoptosis. In the treated cells, the expression of p21 (WAF1/CIP1) increased and that of ␣-fetoprotein (AFP) decreased. These characteristic changes were also observed with 5 other human HCC cell lines with or without mutation of the p53 gene. The abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 14 publications
3
30
0
7
Order By: Relevance
“…Previous studies indicate that the effect of butyrate and other histone deacetylase inhibitors on cells closely corresponds to the effects of p21 Waf1/Cip1 expression in the regulation of G1 (Hunter & Pines 1994), S (Ogryzko et al 1997) and G2 (Coradini et al 1997, Lallemand et al 1999) phases of the cell cycle (Hassig et al 1997). The major mechanism for butyrate-induced cell cycle arrest is reported to be through upregulation of p21 Waf1/Cip1 in various cell systems, including hepatocellular carcinoma cells (Yamamoto et al 1998), colon cancer cells (Nakano et al 1997, Siavoshian et al 1997, Archer et al 1998, Litvak et al 1998, prostate cancer cells (Huang et al 1999) and breast cancer cells (Lallemand et al 1999). In contrast, Vaziri et al (1998) …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies indicate that the effect of butyrate and other histone deacetylase inhibitors on cells closely corresponds to the effects of p21 Waf1/Cip1 expression in the regulation of G1 (Hunter & Pines 1994), S (Ogryzko et al 1997) and G2 (Coradini et al 1997, Lallemand et al 1999) phases of the cell cycle (Hassig et al 1997). The major mechanism for butyrate-induced cell cycle arrest is reported to be through upregulation of p21 Waf1/Cip1 in various cell systems, including hepatocellular carcinoma cells (Yamamoto et al 1998), colon cancer cells (Nakano et al 1997, Siavoshian et al 1997, Archer et al 1998, Litvak et al 1998, prostate cancer cells (Huang et al 1999) and breast cancer cells (Lallemand et al 1999). In contrast, Vaziri et al (1998) …”
Section: Discussionmentioning
confidence: 91%
“…It is a potent growth inhibitor and initiates cell differentiation in several cell types, including breast cancer cells in vitro (Coradini et al 1997, Velázquez et al 1997, Gleave et al 1998, Yamamoto et al 1998. Although the molecular mechanisms by which butyrate exerts its effects are still unclear, it is known to induce a number of alterations within the nucleus, including histone hyperacetylation (de Haan et al 1986, Archer & Hodin 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, treatment failure is frequent and results in high recurrence rates with short survival times (5-7). Histone deacetylase inhibitors (HDACi), including sodium butyrate, are potent inducers of cell growth arrest, differentiation, or apoptosis in a variety of transformed cell lines, including hepatocellular carcinoma, and in intrahepatic metastasis-bearing animals (8,9). Their mechanism of action is based on their ability to inhibit the activity of histone deacetylase enzymes (HDACs); these enzymes, as opposed to histone acetyltransferases, are involved in the regulation of gene expression by determining the degree of acetylation of histones, the core proteins of the nucleosomal structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that HDAC inhibitors exert differentiation effects on many types of cancer cells, including hepatocellular carcinoma (8,39,40), breast cancer (39) and human prostate cancer cells (41). Herein we demonstrated that the HDAC inhibitors 4-PB and TSA possess growth-inhibitory, unique differentiation and pro-apoptotic effects on human glioblastoma cell lines of different cellular origin.…”
Section: Discussionmentioning
confidence: 99%